The Eastern Tropical Pacific Marine Corridor (CMAR): The Emergence of a Voluntary Regional Cooperation Mechanism for the Conservation and Sustainable Use of Marine Biodiversity Within a Fragmented Regional Ocean Governance Landscape - Enright, Sarah Ryan; Meneses-Orellana, Ricardo; Keith, Inti (Frontiers in Marine Science, 2021)
The San Jose Declaration formally established the Eastern Tropical Pacific Marine Corridor (CMAR) in 2004, a voluntary regional cooperation mechanism created by the coastal States of Ecuador, Costa Rica, Colombia, and Panama in response to anthropogenic pressures in the Eastern Tropical Pacific, one of the most productive and biodiverse oceans in the world. This article will explain how, in the absence of a coherent, overarching regional ocean governance framework, these four coastal States came together to create a regional cooperation mechanism for the conservation and sustainable use of marine biodiversity in the Eastern Tropical Pacific. The key normative features of CMAR will be examined, as well as legal and governance challenges, such as its non-binding nature, large scale, limited sectoral engagement, and insufficient resources. The analysis will be couched within a discussion of the wider regional ocean governance framework, which remains fragmented, with gaps and overlaps in terms of membership, mandates and geographic coverage. Possibilities for integration, and the potential impact of a new treaty protecting biodiversity beyond national jurisdiction (BBNJ), will also be considered.